Case Report: Hyperammonemic Encephalopathy Linked to Ureaplasma spp. and/or Mycoplasma hominis Systemic Infection in Patients Treated for Leukemia, an Emergency Not to Be Missed - Delafoy, Manon; Goutines, Juliette; Fourmont, Aude-Marie; Birgy, André; Chomton, Maryline; Levy, Michaël; Naudin, Jérôme; Zafrani, Lara; Le Mouel, Lou; Yakouben, Karima; Cointe, Aurélie; Caseris, Marion; et al. (Frontiers in Oncology, 2022)
Background Hyperammonemic encephalopathy caused by Ureaplasma spp. and Mycoplasma hominis infection has been reported in immunocompromised patients undergoing lung transplant, but data are scarce in patients with hematological malignancies. Case Presentation We describe the cases of 3 female patients aged 11–16 years old, developing initially mild neurologic symptoms, rapidly evolving to coma and associated with very high ammonia levels, while undergoing intensive treatment for acute leukemia (chemotherapy: 2 and hematopoietic stem cell transplant: 1). Brain imaging displayed cerebral edema and/or microbleeding. Electroencephalograms showed diffuse slowing patterns. One patient had moderate renal failure. Extensive liver and metabolic functions were all normal. Ureaplasma spp. and M. hominis were detected by PCR and specific culture in two patients, resulting in prompt initiation of combined antibiotics therapy by fluoroquinolones and macrolides. For these 2 patients, the improvement of the neurological status and ammonia levels were observed within 96 h, without any long-term sequelae. M. hominis was detected post-mortem in vagina, using 16S rRNA PCR for the third patient who died of cerebral edema. Conclusion Hyperammonemic encephalopathy linked to Ureaplasma spp. and M. hominis is a rare complication encountered in immunocompromised patients treated for acute leukemia, which can lead to death if unrecognized. Combining our experience with the few published cases (n=4), we observed a strong trend among female patients and very high levels of ammonia, consistently uncontrolled by classical measures (ammonia-scavenging agents and/or continuous kidney replacement therapy). The reversibility of the encephalopathy without sequelae is possible with prompt diagnosis and adequate combined specific antibiotherapy. Any neurological symptoms in an immunocompromised host should lead to the measurement of ammonia levels. If increased, and in the absence of an obvious cause, it should prompt to perform a search for Ureaplasma spp. and M. hominis by PCR as well as an immediate empirical initiation of combined specific antibiotherapy.